Authigenic uranium preservation and bottom water oxygenation in the Scotia Sea - Hallmaier, Moritz; Gutjahr, Marcus; Lippold, Jörg; Hemming, Sidney R.; Gerber, Lukas; Weber, Michael E.; Eisenhauer, Anton (Geochemistry, geophysics, geosystems, 2025)
Sedimentary uranium (U) and thorium (Th) isotopes are invaluable proxies to assess bottom water redox conditions, site-specific sediment focusing and vertical rain rates. We investigate if authigenic uranium (aU) can serve as a proxy for bottom water ventilation at International Ocean Discovery Program Site U1537 in the Scotia Sea and we provide Th-normalized vertical rain rates and focusing factors. The presented data set is complemented by bulk sediment δ234U, porewater U concentrations and biogenic barium. Furthermore, we introduce a method to check temporal variations in the detrital factor for the calculation of aU by comparing measured and modeled δ234U. We observed partial uranium remobilization in the core for sections older than 70 ka, identified by δ234U anomalies and porewater U concentrations. During interglacials, the accumulation of aU in the sediment is regulated by the decomposition of substantial quantities of organic matter, ultimately controlled by high export productivity and associated high particulate organic carbon fluxes. Conversely, during glacial times, low export productivity coincides with low aU concentrations, suggesting well-oxygenated bottom waters. However, during the Last Glacial Maximum, a rise in aU likely indicates reduced ventilation, suggesting an absence of Weddell Sea Deep Water and/or enhanced water column stratification between 23 and 17.5 ka.